Performance evaluation of the global airline industry under the impact of the COVID-19 pandemic: A dynamic network data envelopment analysis approach - Wu, Sijin; Kremantzis, Marios Dominikos; Tanveer, Umair; Ishaq, Shamaila; O'Dea, Xianghan; Jin, Hua (Journal of air transport management, 2024)
The COVID-19 pandemic posed unprecedented challenges to the airline industry, necessitating a focus on maintaining high efficiency for profitability. This study assesses the efficiency of 26 international airlines from 2019 to 2022 using a dynamic network data envelopment analysis (DNDEA) methodology. The model accounts for the dynamic effect between two consecutive periods and incorporates an internal structure to evaluate airline performance across multiple dimensions. It enables the assessment of overall, period-specific, and stage-specific efficiencies. The findings reveal that while overall efficiency is moderately high on average, no airline achieved full efficiency during the pandemic. Efficiency decreased notably from 2019 to 2020, with a partial recovery but not a return to pre-pandemic levels by 2022. Operational performance remains satisfactory and stable, while service and financial performance exhibit lower efficiency, especially among low-cost airlines compared to full-service counterparts. Additionally, the study explores airlines' environmental impact by considering greenhouse gas emissions. Comparative analysis with a dynamic DEA model without internal structure highlights theoretical contributions, and the study offers managerial insights for airline leaders and policymakers. •COVID-19 Impact: Unprecedented challenges for global airlines.•Dynamic Network DEA: Methodology for assessing airline efficiency.•Performance Trends: Efficiency decrease from 2019 to 2020, partial recovery by 2022.•Comparative Analysis: Operational, service, financial, and environmental efficiencies.•Managerial Insights: Practical recommendations for enhancing airline efficiency.